A apreciação do gênero poético em contexto não escolar: uma construção de saberes em uma pesquisa de ação colaborativa - Adriane de Oliveira e Silva (2012)
This research aims to analyze a practice of work with the poetic genre outside the school context, in an attempt to find arguments that can contribute to the reflection on the relationship of children to poetry. It is an analysis of a study called "Workshops of Poetry -Letters and Lace", developed with two classes of 4th year students from a Municipal School, which services children living in the slum Aglomerado da Serra. These workshops, promoted by a partnership with Lace- Social Support Association, with headquarters at Mangabeiras park, were elaborated upon the school's demand. The expectation was envisaged that the work could contribute to the development of better relations between students and their writing and reading skills, also allowing a better interaction between st udents themselves and with the knowledge in general. For the development of this research, the data was collected in the forms of video, audio, photographic records, planning and field diary about the workshops performed, and records of written pieces by t he students. As analysis methodology, we adopted action research with a participatory / collaborative character. The methodology of action research aims to collaborate with an analysis of what is being done, put into action, seeking to achieve those goals. It was intended in this study to observe and analyze the situations experienced by students in the workshops Letters and Link, which have shown their interest by the appreciation of poetic text and favored the presence of the word among them, lived on the facts, feelings and emotions.